C(sp3)–H versus C(sp3)–C(sp) in Activation of Propargylic Amines under Transition-Metal Catalysis - Nakamura, Hiroyuki (Synlett, 2015)
Transition-metal-catalyzed C–H and C–C bond activation procedures have attracted significant interest as environmentally friendly processes for organic synthesis. This account summarizes transition-metal-catalyzed transformations of propargylic amines through C(sp3)–H and C(sp3)–C(sp) activation, including hydrogen transfer, deacetylenative homocoupling, fragment exchange, and redox cross-dehydrogenative coupling (CDC). The generation of iminium intermediates is essential for the current transformations based on propargylic amines.1 Introduction2 Synthesis of Allenes from Propargylic Amines through Palladium-Catalyzed Hydrogen-Transfer Reactions2.1 Propargylic Amines as Allenyl Anion Equivalents2.2 Synthesis of Allenyl Carbinols2.3 Synthesis of Heterocyclic Allenes2.4 Mechanistic Study2.5 One-Pot Synthesis of Allenes from Aryl Halides3 Substitution Reactions of Propargylic Amines through Copper(I)-Catalyzed C(sp)–C(sp3) Bond Activation3.1 Substitution Reactions of Propargylic Amines with Secondary Amines3.2 Substitution Reactions of Propargylic Amines with 1-Alkynes3.3 Deacetylenative Coupling with Various Propargylic Amines4 Zinc(II)-Catalyzed Redox Cross-Dehydrogenative Coupling of Propargylic Amines and Terminal Alkynes5 Conclusion
Keywords: propargylic amines; C–H activation; C–C activation; palladium; copper; zinc; allenes; 1,6-enynes